DESAIN PROGRAM UNGGULAN PADA SISTEM ELECTRONIC-GOVERNMENT PEMERINTAH KABUPATEN SELUMA - Arius Satoni Kurniawansyah; Rizka Tri Alinse (Universitas Asahan, 2019)
Abstract - The presence of an Electronic Government is information and telecommunications technology for efficient and effective government administration, as well as providing transparent and satisfying public services. The integration of information systems today greatly influences public institutions such as regional and central government. The current regional government system has begun to be integrated in a technology that can be controlled from the central government. An example is the application of electronic-government (e-Gov) which began to be implemented in Indonesia and in several regions. The stages of the research method are Application for permission for research from the Research and Community Service Institute of Dehasen University Bengkulu, Research Permit from Seluma Regency DPMPPTSP, Government data collection both manual and computerized, Grouping of Government data namely Regional Superior Program Name per each OPD in Seluma Regency in 2019. A cross-sectoral development program to create superior and prosperous Seluma District people by improving infrastructure, facilities and infrastructure, including tourism and leading sectors and optimizing superior products. One solution and alternative that promises to create transparency in realizing good governance is with an electronic government management system (e-government). Management of institutions / agencies electronically for both private and government in addition to increasing transparency, can also improve the quality of work produced by the Regional Government.Abstrak - Hadirnya sebuah Electronic Government adalah teknologi modern dewasa ini sebagai pelayanan secara elektronik bagi pemerintah dengan memberikan pelayanan yang terbaik untuk masyarakat. Terintegrasinya sistem informasi dewasa ini sangat mempengaruhi lembaga-lembaga publik seperti pemerintah daerah dan Pemerintah Pusat. Sebuah system pemerintah sekarang sudah terintegrasi dalam sebuah teknologi yang dapat monitor oleh pemerintahan pusat. Contohnya adalah sekarang penerapan electronic-government (e-Gov) telah di implementasikan di Indonesia dan di beberapa daerah. Tahapan metode penelitiannya adalah Permohonan izin untuk penelitian dari Lembaga LPPM Universitas Dehasen Bengkulu, Izin penelitian dari DPMPPTSP Kabupaten Seluma, Pengumpulan data Pemerintahan baik yang masih manual maupun yang sudah terkomputerisasi, Pengelompokan data Pemerintahan yakni Nama Program Unggulan Daerah per setiap OPD di Kabupaten Seluma Tahun 2019. Program pembangunan lintas sektoral guna mewujudkan masyarakat Kabupaten Seluma yang unggul dan sejahtera dengan meningkatkan infrastruktur, sarana dan prasarana, termasuk wisata serta sektor unggulan dan optimalisasi produk unggulan. Ada sebuah alternative yang dapat digunakan untuk membangun sebuah transparansi dalam mewujudkan Pemerintahan yang baik adalah dengan sebuah e-government. Pengelolaan Lembaga secara digital baik untuk swasta maupun Pemerintah selain dapat meningkatkan transparansi, juga dapat meningkatkan kualitas kerja yang dihasilkan oleh Pemerintah Daerah.